Gender, Race and Diversity: Professional Trajectories of Black Businesswomen - Jaime, Pedro; Silva Hein, Audrey (Organizações & Sociedade, 2021)
Since the beginning of this century diversity management has been present as an important topic of studies in the field Administration in Brazil. However, research on this topic that focuses on the Black population is still scarce. In order to contribute to fill this gap, this article brings the results of a socio-anthropological investigation conducted through the biographical method and ethnographic fieldwork on the professional trajectories of two generations of Black businesswomen. These trajectories were analyzed from the societal contexts that framed them and considering gender, race and class in an intersectional perspective. The results reveal that the career paths of the second generation were built in a much more favorable societal context. However, they also show that we are still very far from gender and racial equality in the Brazilian corporate world.